Advances in managing organic matter in turfgrass ecosystems - Kowalewski, Alec (Burleigh Dodds Series in Agricultural Science, 2023)
Organic matter (OM) management is a critical component in sustainable turfgrass management. Organic matter improves the soils' ability to hold nutrients and water. However, when OM accumulation is excessive, several detrimental effects develop. Turfgrass is a tillering plant, producing a considerable amount of lateral growth, which will cause inordinate OM accumulation. The objectives of this chapter are to outline how OM effects turfgrass, the available methods for monitoring and measuring OM accumulation, outline correlations between OM levels and disease activity/microbial populations, and identify successful OM management practices.